2021
DOI: 10.1038/s41598-021-88871-8
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of weak magnetic field effects on oscillating reactions

Abstract: We explore the possibility that chemical feedback and autocatalysis in oscillating chemical reactions could amplify weak magnetic field effects on the rate constant of one of the constituent reactions, assumed to proceed via a radical pair mechanism. Using the Brusselator model oscillator, we find that the amplitude of limit cycle oscillations in the concentrations of reaction intermediates can be extraordinarily sensitive to minute changes in the rate constant of the initiation step. The relevance of such amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It should also be pointed out that including these interactions can reduce the predicted effect size [ 61 , 440 ]. However, this may be balanced by potential amplification effects in the biological systems [ 59 , 594 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be pointed out that including these interactions can reduce the predicted effect size [ 61 , 440 ]. However, this may be balanced by potential amplification effects in the biological systems [ 59 , 594 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the work of Tyson et al [ 592 ], the authors used a simple mathematical model for Drosophila ’s circadian clock, as shown in figure 6 a (for more detailed models see [ 593 ]). Similar to the work of Player et al [ 594 ], they introduced the effects of applied magnetic fields and hyperfine interactions on the circadian clock process by modifying the corresponding rate representing the role of cryptochrome’s light activation and, hence, proteolysis of protein. Based on these models and using equations ( 3.19 ) and ( 3.20 ), they reproduced the experimental findings of the magnetic field [ 583 ] and lithium effects [ 584 ] on Drosophila ’s circadian clock, as shown in figure 6 c , d .…”
Section: Studies Of the Potential Role Of Radical Pairs In The Brainmentioning
confidence: 99%
“…We are investigating the mechanism of activating blast-furnace cement (from now on BFC) by introducing magnetized ferromagnetic dust additive (from now on MFDA) into their composition. The magnetic fields effect on chemical reactions has been well studied and, in particular, considered in works [15][16][17][18]. Magnetic fields affect spin dynamics and control the spin multiplicity of radical pairs of substances involved in a chemical reaction.…”
Section: Research and Publications Analysismentioning
confidence: 99%
“…6a (For more detailed models see Ref 588 ). Similar to the work of Player et al 589 , they introduced the effects of applied magnetic fields and hyperfine interactions on the circadian clock process by modifying the corresponding rate representing the role of cryptochrome's light activation and, hence, proteolysis of protein. Based on these models and using Eqs.…”
Section: Magnetic Field and Lithium Effects On Circadian Clockmentioning
confidence: 99%